Outbreaks in the adult ICUs. Issue 4 (August 2017) - Al-Dorzi, Hasan M.; Arabi, Yaseen M.
Abstract : Purpose of review: Infectious disease outbreaks in the critical care setting are common and serious consequence. This article reviews and summarizes recent outbreaks in the adult ICUs. Recent findings: Outbreaks of multidrug-resistant bacteria, fungi, and emerging viruses in ICUs from different countries are common. Outbreak investigation relies on epidemiologic methods, microbiologic studies, and molecular typing methods. Overuse of antibiotics, gaps in implementing infection prevention measures, and contaminated environment are common causes of ICU outbreaks. ICU staff awareness of and preparedness for such outbreaks are crucial for outbreak prevention and control. Specific infection control measures vary according to outbreak transmission mode and cause. Summary: Outbreaks remain a significant threat to healthcare systems. Proper implementation of infection prevention practices and judicious use of antibiotics are needed for outbreak prevention in adult ICUs. Surveillance, proper outbreak investigation, adherence to infection prevention and control measures, and thorough disinfection of contaminated areas are required to successfully manage outbreaks.